2012
DOI: 10.7314/apjcp.2012.13.4.1657
|View full text |Cite
|
Sign up to set email alerts
|

Fucosyltransferase IV Enhances Expression of MMP-12 Stimulated by EGF via the ERK1/2, p38 and NF-kB Pathways in A431Cells

Abstract: Fucosyltransferase IV (FUT4) has been implicated in cell adhesion, motility, and tumor progression in human epidermoid carcinoma A431 cells. We previously reported that it promotes cell proliferation through the ERK/MAPK and PI3K/Akt signaling pathways; however, the molecular mechanisms underlying FUT4-induced cell invasion remain unknown. In this study we determined the effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…To determine whether the ERK pathway is also involved in the inhibition of p65 phosphorylation by melatonin, we examined the ERK kinase pathway, as well as p38 and JNK activity. In fact, under the same conditions, the ERK pathway did not inhibit the release of activated NF-κB, a result that contrasts with data showing that the phosphorylation of ERK1/2 regulates the phosphorylation (and activation) of NF-κB [47]. Indeed, an ERK inhibitor attenuated the forcemediated stimulation of NF-κB DNA binding in human periodontal ligament fibroblasts but not in the presence of a JNK or p38 MAPK inhibitor [48].…”
Section: Melatonin Enhances the Effectiveness Of Cisplatin By Supprescontrasting
confidence: 53%
“…To determine whether the ERK pathway is also involved in the inhibition of p65 phosphorylation by melatonin, we examined the ERK kinase pathway, as well as p38 and JNK activity. In fact, under the same conditions, the ERK pathway did not inhibit the release of activated NF-κB, a result that contrasts with data showing that the phosphorylation of ERK1/2 regulates the phosphorylation (and activation) of NF-κB [47]. Indeed, an ERK inhibitor attenuated the forcemediated stimulation of NF-κB DNA binding in human periodontal ligament fibroblasts but not in the presence of a JNK or p38 MAPK inhibitor [48].…”
Section: Melatonin Enhances the Effectiveness Of Cisplatin By Supprescontrasting
confidence: 53%
“…Hence, our results are consistent with the notion that H2O2 plays a pivotal role in PKC activation via ROS generation. It has been shown that MAPK exists downstream of PKC and regulates many related transcription factors, including NF-κB and β-catenin, in several cell types, including human UCBMSCs and mouse ESCs (Yun et al, 2009;Yang et al, 2012;Lee do et al, 2013;Priyanka et al, 2013). We found that H2O2 was able to induce ERK and p38 MAPK activation, thereby stimulating NF-κB and β-catenin activation.…”
Section: Figurementioning
confidence: 52%
“…24 We also found that FUT4 had a critical role in the MAPK pathway by mediating EGF-induced NF- κ B activation and increasing expression of MMP-12. 25 Given that FUT4 may have an important role in tumor metastasis, we were prompted in this study to explore its role in the induction of EMT in breast cancer cells. Based on our results, we propose that FUT4, via activation of NF- κ B and PI3K/Akt-GSK3 β signaling, enhances the expression of Snail, leading to acquisition of the mesenchymal phenotype in breast cancer cells.…”
mentioning
confidence: 99%